Morphological revision of Tulasnellaceae, with two new species of Tulasnella and new records of Tulasnella spp. for Ecuador - Piepenbring, M. (2015)
Due to ambiguous morphological and molecular characteristics, species of Tulasnellaceae are difficult to organize taxonomically. In this study a morphological revision of the family and 30 reinvestigated morphospecies of Tulasnella are presented. Illustrations, descriptions, statistical analysis, and discussions of the species are based on exsiccata from fungaria and own specimens collected in Ecuador and Germany. A dichotomous key to genera of Tulasnellaceae and the species of Tulasnella described in the present publication is compiled. Tulasnella andina from Ecuador and Tulasnella kirschneri from China are presented as species new to science. Tulasnella cruciata was described from Australia from a basidioma grown in culture and a species similar but not identical to this species was obtained from a basidioma found in herbarium material for the first time. Tulasnella aff. eichleriana and T. violea are reported for the first time from Ecuador. Phylogenetic placements of the new species T. andina and new records for Ecuador are presented based on sequences previously published by us. The morphological reinvestigations exemplify a vast intra-specific structural variability in species of Tulasnella and call for further specimens for morphological analysis and molecular data to define species.